EVALUASI SISTEM INFORMASI PENJUALAN PADA PT ARORI JAYA - Gui, Anderes; Maryanie, Maryanie; Octorian, Melvin; Nurhadi, Nurhadi; William, William (CommIT (Communication and Information Technology) Journal, 2009)
The purpose of this study was to determine the level of internal control at PT Arori Jaya and provided recommendation to the weaknesses found. The method used is the method of interview, check list, observation, and documentation study. The results of the evaluation system sale information found weaknesses of each control, where there are weaknesses that allow the potential risks that may occur as well as the recommendations as necessary remedial action. The conclusion is based on the evaluation results have been obtained on credit sales information system controls at the company, still need improvement. With the internal control system of better information, it is expected the company to ensure protecting data and information from every threat that may arise.Keywords: evaluation, credit sales information system